Multilevel Comparisons of Hospital Discharge among Older Adults with a Fall‐Related Hospitalization. (31st August 2017) - Towne, Samuel D.; Fair, Kayla; Smith, Matthew Lee; Dowdy, Diane M.; Ahn, SangNam; Nwaiwu, Obioma; Ory, Marcia G.
Abstract : Objective: We examined multilevel factors associated with hospital discharge status among older adults suffering a fall‐related hospitalization. Data Sources: The 2011–2013 ( n = 131, 978) Texas Inpatient Hospital Discharge Public‐Use File was used. Study Design/Methods: Multilevel logistic regression analyses estimated the likelihood of being discharged to institutional settings versus home. Principal Findings: Factors associated with a greater likelihood of being discharged to institutional settings versus home/self‐care included being female, white, older, having greater risk of mortality, receiving care in a non‐teaching hospital, having Medicare (versus Private) coverage, and being admitted from a non‐health care facility (versus clinical referral). Conclusions: Understanding risk factors for costly discharges to institutional settings enables targeted fall‐prevention interventions with identification of at‐risk groups and allows for identifying policy‐related factors associated with discharge status.